Productivity and limitations of plantain (Musa spp. cv AAB) production in compound gardens in southeastern Nigeria - Nweke, F.; Njoku, J.; Wilson, G. (1988)
This paper, based on a socio-economic survey, investigates the productivity of compound plantain production and constraints to large scale production on the basis of the compound production method. The paper shows that production under the compound system results in nearly four times as much yield as in non-compound system. This is attributed to regular application of kitchen and other compound wastes, close cultural attention given by the farmer, and to nutrient recycling to the benefit of the compound plantains from deep rooted perennial tree crops inter-planted large scale production employing the compound methods is limited by supply of organic matter and by available market for plantains. Available market can be expanded by increased production during the slack period of June to September when output is low and by packaging to reduce damage in transit to take advantage of distant markets.